TRANSFORMASI SPIRITUAL TOKOH UTAMA DALAM NOVEL ATEIS KARYA ACHDIAT KARTAMIHARDJA - Agus Yulianto (Balai Bahasa Nusa Tenggara Barat, 2017)
The aim of this research is to know the reason of Hasan, the protagonist being anatheist and how the spiritual changing process from a devoted muslim into an atheistand how Islamic thougth denies ateism. The problems in this research are 1) whatcausing Hasan becoming an atheist; 2) how Hasan spiritually changes from adevoted muslim into an atheist; 3) how Islamic thought denies atheism.This studyuses qualitative descriptive method in literature review. Based on the study, it isconcluded that the causes of Hasan’s spiritual changing from a devoted muslim intoan ateist are his weaknees in Islamic thinking tradition and love factor which doesnot follow religious norms and ethics.